Laparoscopic Versus Open Mesh Repair of Inguinal Hernia for Military Personnel - Hossain, Mohammad Monir; Hossain, S M Eqbal; Hossain, Md Delowar (Bangladesh Armed Forces Medical Journal, 2024)
Background: An organ or fatty tissue, like the colon, might abnormally emerge through the wall of the cavity in which it normally dwells, a condition known as a hernia. Inguinal hernia repair is among the most frequently done procedures by surgeons worldwide. Treatment includes pure tissue repairs to prosthetic repairs under open or laparoscopic approach. Though so many options are available but none is superior to others. Aim of the study is to compare the effectiveness of laparoscopic hernia repair with open mesh hernia repair. Methods: The study was a comparative cross-sectional study. The study, which took place between 2016 and 2018, involved 100 cases in the General Surgery department of Combined Military Hospital (CMH), Savar (30 cases of laparoscopic hernioplasty and 70 cases of open hernioplasty). Purposive sampling technique was used to collect data. Data were collected during follow up of patients by using a semi-structured questionnaire. Data were analysed by using Statistical Package for the Social Sciences (SPSS) version 26.0. Informed written consent were obtained from the patients and ethical issues were duly addressed. Results: There were 100 patients in the study, 30 of whom were assigned to group A (the laparoscopic group) and 70 to group B (the open group). In group A, the mean operating time was 103.67±23.57 minutes, while in group B, it was 50.26±2.57 minutes. In group A, there was a decrease in pain scores, with 90% of patients reporting 1-2 (mild discomfort). Three people are in excruciating pain. Conclusion: Inguinal hernia repair is a frequently performed general surgery treatment. Because of the large socio-economic impact of inguinal hernia repair, it is the responsibility of the surgeon to consider the most advantageous approach in each given situation. For all patients needing elective hernioplasty, laparoscopic, non-randomized, pre-peritoneal mesh repair for inguinal hernias is a safe, effective method that has clear advantages over open mesh repair. Bangladesh Armed Forces Med J Vol 56 No (2) December 2023, pp 17-23